2018
DOI: 10.1002/smll.201804436
|View full text |Cite
|
Sign up to set email alerts
|

Removal Efficacy of Opportunistic Pathogens and Bacterial Community Dynamics in Two Drinking Water Treatment Trains

Abstract: Figure 4. Two trains of drinking water treatment processes. The symbol ( ) indicates sampling locations of water samples. Train I and II used the same water source. 1804436 (10 of 10) www.advancedsciencenews.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…and Mycobacterium spp., are not completely removed by drinking water treatment processes. 45 In this study, a high FOD of Legionella (92.3%) in biofilms was observed, which was comparable to those found in drinking water in the same city. 21,46 In contrast with another study, a survey of Legionella in pipe biofilms obtained from a chloramine-containing DWDS in the United States showed that no Legionella spp.…”
Section: ■ Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…and Mycobacterium spp., are not completely removed by drinking water treatment processes. 45 In this study, a high FOD of Legionella (92.3%) in biofilms was observed, which was comparable to those found in drinking water in the same city. 21,46 In contrast with another study, a survey of Legionella in pipe biofilms obtained from a chloramine-containing DWDS in the United States showed that no Legionella spp.…”
Section: ■ Discussionsupporting
confidence: 83%
“…The keystone taxa play key roles in maintaining the stability of the biofilm community strucuture, and their disappearance may cause networks to disassemble . Nitrospirae was regarded as one of the core phyla in the biofilm microbiome, implying that N-related biological processes occur in biofilms. , The presence of Nitrospira in pipe biofilms may be related to residual nitrogenous compounds in upstream water. The use of disinfection, such as chlorine and chloramine, in water systems also may influence biofilm community structure.…”
Section: Discussionmentioning
confidence: 99%
“…The top five most abundant families identified from the 3,821 OTUs were Burkholderiaceae, Sphingomonadaceae, unclassified Alphaproteobacteria, unclassified Corynebacteriales, and Mycobacteriaceae (descending order of number of OTUs in a family) (Supplementary Table 9). Mycobacteriaceae contains a single genus Mycobacterium which is an important drinking water opportunistic pathogen (Good, 1985;Marciano-Cabral et al, 2010;Lu et al, 2017;Wang et al, 2019;Zhang and Lu, 2021). For both cold and hot tap water, the relative abundance of Burkholderiaceae (one dominant family in drinking water and PPSs) (Zeng et al, 2013;Buse et al, 2014;Ferro et al, 2019;Vavourakis et al, 2020) and Xanthobacteraceae (associated with nitrogen fixation) (Oren, 2014) obviously dropped in the second draws (compared with the first draws) (Figure 3).…”
Section: The Bacterial Community Compositions Of Cold Tap Hot Tap and Shower Water Were Distinctmentioning
confidence: 99%
“…Among these microorganisms are some waterborne pathogens or opportunistic pathogens such as Legionella and Mycobacterium species, which pose a public health risk as they cause infectious diseases [16]. Previous studies have evaluated bacterial and fungal diversity at various stages in conventional water treatment processes [17,18], have elucidated spatiotemporal changes in bacterial communities [19,20], and have investigated the occurrence of pathogenic microorganisms in drinking water systems [21]. For example, Tiwari et al analyzed the spatial and seasonal dynamics of bacterial communities within the Kokemäenjoki River watershed [20].…”
Section: Introductionmentioning
confidence: 99%